(untitled) (Qawanin Jurnal Ilmu Hukum, 2024)
The purpose of this research is to find out and analyze the role of notaries in distributing heirs’ rights and to find out and analyze the responsibilities of notaries in resolving heirs’ rights problems. The research method used in this research is empirical research, namely research using field data as the main data source, such as the results of interviews and observations. The data analysis technique used is carried out by collecting data through the results of interviews submitted and library materials or secondary data which includes primary legal materials and tertiary legal materials in the form of documents and applicable laws and regulations.The results of the research reveal that regulating the rights of Notary heirs is an important thing for people’s lives, so that the behavior and actions of Notaries in carrying out their professional positions are vulnerable to abuse that can be detrimental to society, so it is very necessary to carry out guidance and supervision of notaries, regarding the responsibilities of Notaries, Notaries. has a very big responsibility in making the inheritance certificate deed. And the Notary must be careful in making a deed because the Notary must take full responsibility based on the law if the deed, he makes causes losses to the parties. Suggestions given by the author for notaries in carrying out every deed they must prioritize the common interest rather than the interests of one party, so that the existence of each party is not ignored and obtains a balanced position while reducing disputes between heirs. Meanwhile, the Notary must have proper control in making the deed regarding the duties and authority of the notary as an authentic deed maker Abstrak: Penelitian ini bertujuan Untuk mengetahui dan menganalisis peran notaris dalam pembagian hak ahli waris dan untuk mengetahui dan menganalisis tanggung jawab notaris dalam menyelesaikan permasalahan hak ahli waris. Metode penelitian yang digunakan dalam penelitian ini yaitu bersifat penelitian empiris. Hasil penelitian mengungkapkan dalam pengaturan hak ahli waris Notaris merupakan hal yang penting bagi kehidupan masyarakat, sehingga perilaku dan perbuatan Notaris dalam menjalankan jabatan profesinya rentan terhadap penyalahgunaan yang dapat merugikan masyarakat, sehingga sangat diperlukan pelaksanaan pembinaan dan pengawasan terhadap notaris, mengenai tanggung jawab Notaris, Notaris memilki tanggung jawab yang sangat besar dalam pembuatan akta keterangan waris. Dan Notaris haruslah berhati-hati dalam membuat akta karena dimana Notaris harus bertanggung jawab penuh berdasarkan Undang-Undang akta yang dibuatnya menimbulkan kerugian bagi para pihak. Rekomendasi yang diberikan penulis Bagi notaris dalam melaksanakan setiap pembuatan akta wajib lebih mementingkan kepentingan bersama dari pada kepentingan satu pihak, sehingga keberadaan masing-masing pihak tidak terabaikan dan mendapatkan kedudukan yang seimbang beserta mengurangi pertikaian antar ahli waris. Adapun Notaris harus memegang kendali betul dalam pembuatan akta yang berkenaan dengan tugas dan kewenangan notaris sebagai pembuat akta autentik. Kata Kunci: Notaris; Hak Ahli Waris; Warisan Tanah; Properti;